Web Server Future Planning Decision Analysis - Fuzzy Linguistic Weighted Approach - Chin, Wen Cheong; Hua Yeow, Kelvin Wen; Ng, Kah Leong (Malaysian Journal of Computer Science, 2000)
In this paper, fuzzy weighted approach is used to solve the multi-criteria decision making problem in a Web server system. The assessments of Web server by Web administrators are assigned using linguistic terms. The overall assessments of alternatives, with respect to every criteria, are allowed by different weights using a symmetrical triangular fuzzy number with fixed interval confidence. Web administrators’ inconsistent optimistic levels can be flexibly assigned by different desired index of optimism.